Health Reforms in Pursuit of Universal Health Coverage: Lessons from Kenyan Bureaucrats - Wangari Ng'ang'a; Mercy Mwangangi; Agnes Gatome-Munyua (Taylor & Francis Group, 2024)
In this commentary, two members of the technical teams that led Kenyan health reforms reflect on progress made in the country's journey toward universal health coverage during President Uhuru Kenyatta's second term (2017 to 2022). The authors discuss how key decisions were made while balancing multiple considerations such as: maintaining the technical fidelity of the reforms to achieve objectives, accounting for the context of previous reforms, and making necessary trade-offs between technical and political pressures. They share three lessons, contextualized with African proverbs, for others implementing health reforms. First: "The person who does not seize today's opportunity will also be unable to seize tomorrow's opportunity"-that is, act quickly when opportunities arise. Second: "The person who cannot dance will say, 'The drum is bad!'" This implies that naysayers, especially those who are not part of technical teams, may not understand the reasons behind certain decisions or trade-offs. Reformers must balance different needs, including responding to varied opinions, taking urgent action, generating timely results, making technically sound decisions, and getting the design right. And third: "A bird that flies from the ground onto an anthill does not know that it is still on the ground." This proverb reminds us to not mistake short-term gains for the achievement of long-term goals. Kenya continues to enjoy unprecedented political will to pursue health reforms. For other reformers lucky enough to have political support, the final advice to the technical teams in the driver's seat is to design for delivery ... and then start!